2006
DOI: 10.1111/j.1365-2230.2005.01974.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of folliculosebaceous cystic hamartoma.

Abstract: Folliculosebaceous cystic hamartoma (FSCH) is a rare cutaneous hamartoma composed of dilated folliculosebaceous units associated with mesenchymal elements. Two cases of FSCH with typical histopathological features are reported. Patient 1 was a 60-year-old man presented with a normal skin-coloured asymptomatic nodule on his scalp. Patient 2 was a 70-year-old man with an asymptomatic nodule on his right auricle that had persisted for the previous 15 years. In all, 34 cases of FSCH have been reported in the Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…1,2 A thorough review of the literature revealed a total of 29 cases of primary FSCH arising in 28 patients. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These cases are summarized in Table I. Two cases of secondary FSCH, one arising in a giant nevus lipomatous superficialis 15 and another arising in a port-wine stain, 16 were excluded from the table.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A thorough review of the literature revealed a total of 29 cases of primary FSCH arising in 28 patients. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] These cases are summarized in Table I. Two cases of secondary FSCH, one arising in a giant nevus lipomatous superficialis 15 and another arising in a port-wine stain, 16 were excluded from the table.…”
Section: Discussionmentioning
confidence: 99%
“…Although some cases of giant FSCH have been reported, the vast majority of lesions are 0.5 to 1.5 cm-sized papules or nodules9. Due to its lack of distinctive clinical features, they are often misdiagnosed as other disorders such as intradermal nevus, sebaceous hyperplasia, lipoma and neurofibroma10,11. The differential diagnosis includes STF, steatocystoma and dermoid cyst.…”
Section: Discussionmentioning
confidence: 99%
“…It always presents as a painless, slowly growing single firm papule or nodule with a predilection for the central face [3,4]. Other parts such as the vulva, the nipple, the scrotum, the ear or scalp have been reported for FSCH [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Folliculosebaceous cystic hamartoma was first described by Kimura et al [1] in 1991 as a rare cutaneous hamartoma composed mainly of follicular, sebaceous and mesenchymal elements [1,2]. Folliculosebaceous cystic hamartoma does not have peculiar clinical features [3,4]. Clinicians always suggest cyst-like cutaneous lesion, soft tissue neoplasm, sebaceous gland hyperplasia or melanocytic nevus [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation